2012
DOI: 10.1093/sysbio/sys058
|View full text |Cite
|
Sign up to set email alerts
|

A Total-Evidence Approach to Dating with Fossils, Applied to the Early Radiation of the Hymenoptera

Abstract: Phylogenies are usually dated by calibrating interior nodes against the fossil record. This relies on indirect methods that, in the worst case, misrepresent the fossil information. Here, we contrast such node dating with an approach that includes fossils along with the extant taxa in a Bayesian total-evidence analysis. As a test case, we focus on the early radiation of the Hymenoptera, mostly documented by poorly preserved impression fossils that are difficult to place phylogenetically. Specifically, we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
998
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 796 publications
(1,020 citation statements)
references
References 74 publications
(113 reference statements)
19
998
0
3
Order By: Relevance
“…Similarly high variance under the IGR model was retrieved in analyses of a hymenopteran insect dataset [29]. Plots of rate against time revealed no clear evidence of elevated rates being concentrated in branches near the KPg boundary ( figure 2a,b); indeed, under both the IGR and TK models, rates are highest on branches closer to the root ( figure 2a,b), which accordingly are compressed in time-a similar result was found by Ronquist et al [28] in their analysis of hymenopterans. Perhaps unsurprisingly, molecular rates in these analyses (all under the IGR model; see above) show much less heterogeneity; median rates across different branches spanned a range of approximately 51Â both when only the age of the root was constrained and when the ages of selected internal divergences within Placentalia were also constrained (figure 2a,b; electronic supplementary material, §7).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Similarly high variance under the IGR model was retrieved in analyses of a hymenopteran insect dataset [29]. Plots of rate against time revealed no clear evidence of elevated rates being concentrated in branches near the KPg boundary ( figure 2a,b); indeed, under both the IGR and TK models, rates are highest on branches closer to the root ( figure 2a,b), which accordingly are compressed in time-a similar result was found by Ronquist et al [28] in their analysis of hymenopterans. Perhaps unsurprisingly, molecular rates in these analyses (all under the IGR model; see above) show much less heterogeneity; median rates across different branches spanned a range of approximately 51Â both when only the age of the root was constrained and when the ages of selected internal divergences within Placentalia were also constrained (figure 2a,b; electronic supplementary material, §7).…”
Section: Resultssupporting
confidence: 78%
“…Other studies that have used TE dating have also found that many nodes were estimated to be considerably older than indicated by the fossil record (e.g. [28,31]). Such deep inferred divergences should be treated with caution, given the evidence presented here that the IGR and TK clock models can give implausibly ancient node age estimates when using temporal information provided by fossils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there has been an increasing number of studies employing probabilistic approaches to estimate phylogenies with morphologic data, especially in paleontology (e.g., Wagner, 1998Wagner, , 1999Snively et al, 2004;Pollitt et al, 2005;Clarke and Middleton, 2008;Pyron, 2011;Ronquist et al, 2012;Slater, 2013Slater, , 2015Wright and Stigall, 2013;Lee et al, 2014;Close et al, 2015;Bapst et al, 2016;Gorscak and O'Connor, 2016).…”
Section: Introductionmentioning
confidence: 99%